Grain Intake and Clinical Outcome in Stage III Colon Cancer: Results From CALGB 89803 (Alliance). Issue 2 (30th May 2018) - Brown, Justin C; Zhang, Sui; Niedzwiecki, Donna; Saltz, Leonard B; Mayer, Robert J; Mowat, Rex B; Whittom, Renaud; Hantel, Alexander; Benson, Al; Atienza, Daniel; Messino, Michael; Kindler, Hedy; et al.
Abstract: Background: Energy balance–related risk factors for colon cancer recurrence and mortality—type II diabetes, hyperinsulinemia, inflammation, and visceral obesity—are positively correlated with consumption of refined grains and negatively correlated with consumption of whole grains. We examined the relationship between the consumption of refined and whole grains with cancer recurrence and mortality in a cohort of patients with colon cancer. Methods: We conducted a prospective observational study of 1024 patients with stage III colon cancer who participated in a randomized trial of postoperative chemotherapy. Patients reported consumption of refined and whole grains using a food frequency questionnaire during and six months after chemotherapy. The primary outcome was disease-free survival (DFS). Multivariable-adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated using Cox regression models. All P values are two-sided. Results: During a median follow-up of 7.3 years, 394 patients experienced a DFS event. The hazard ratio for DFS was 1.56 (95% CI = 1.09 to 2.24) for patients consuming three or more servings per day of refined grains compared with patients consuming less than one serving per day ( P trend = .005). The hazard ratio for DFS was 0.89 (95% CI = 0.66 to 1.20) for patients consuming three or more servings per day of whole grains compared with patients consuming less than one serving per day ( P trend = .54). The hazard ratio for DFS of substituting one serving per day of refined grain with one serving per day of whole grain was 0.87 (95% CI = 0.79 to 0.96, P = .007). Conclusions: The choice of grain consumed may be associated with cancer recurrence and mortality. Future studies are necessary to confirm our findings and to inform the design of randomized trials.